P24 Cytokine biomarker profiling in acetaminophen-induced acute liver failure: importance of monocyte chemotactic protein-1 in prognosis and hepatic encephalopathy. (16th November 2010) - Antoniades, H; Mathew, B; McPhail, M; Srirajaskanthan, R; Berry, P; Bernal, W; Hussain, M; Auzinger, G; Wendon, J
Abstract : Introduction: Inflammatory cytokines have recently been described as reflecting severity of liver injury, grade of encephalopathy and prognosis in acute liver failure (ALF). The role of monocyte chemotactic protein-1 and peripheral monocyte count has not been well studied. Method: 35 consecutive patients admitted to our institution with a diagnosis of acetaminophen induced ALF were studied for the effect of a biomarker profile of inflammatory cytokines (IL-4, IL-6, IL-10, MCP-1, TNF-a, IFN-g) levels at admission on grade of hepatic encephalopathy (HE) and prognosis. Modified King's College Criteria (KCC) was used in deciding whether to perform ELT. Assessment of HE and prognostic markers was investigated using logistic regression and receiver operating characteristic (ROC) curve analysis. Results: MCP-1 levels were significantly correlated with standard markers of severity of liver injury (INR: R=0.737, p<0.001; lactate: R=0.772, p<0.001; AST:R=0.545, p<0.001) and with IL-6 (R=0.576, p=0.003) and IL-10 (R=0.679, p<0.001). MCP-1 levels were significantly reduced in spontaneous survivors (1149 (range 168–12 998) compared to patients who died/underwent orthotopic liver transplantation (OLT) (7925 (1694–30 625), p<0.001, Mann–Whitney U test. The area under the ROC curve (AUROC) for MCP-1 and prediction of poor outcome was 0.88 (95% CI 0.68 to 0.97, p<0.001). There was no significant difference in performance of MCP-1 compared with IL-4 (AUROC 0.80 (0.59–0.93)) IL-6 (AUROC 0.83 (0.63–0.95)) or IL-10 (AUROC 0.84 (0.64–0.95) p>0.05 for all; De Long method). MCP-1 performed better than peripheral monocyte count (AUROC 0.75 (0.57–0.85). TNF-α, TGF-β1 and IFN-γ levels did not predict outcome. IL-6 better predicted the development of severe (grade 3–4) HE (AUROC 0.91 (0.72–0.98) compared with MCP-1 (AUROC 0.71 (0.49–0.87), p=0.087 (De Long method)). Conclusion: MCP-1 has similar behaviour to IL-4, IL-6 and IL-10 in outcome prediction in acetaminophen induced acute liver failure and better reflects poor prognosis than peripheral monocyte count. IL-6 may better reflect the severity of HE suggesting different roles for interleukins and MCP-1 in the pathogenesis of the inflammatory milieu in ALF.